تقييم دور قطاع الزراعة في الاقتصاد السوري (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يُعدُّ قطاع الزراعة مكّونا مهما من مكّونات الاقتصاد السوري كونه مصدرا أساسيا للسلع الغذائية الزراعية. ولقد شهد ناتج القطاع الزراعي في سورية تقلبات كبيرة في السنوات الأخيرة نتيجة لتدهور الظروف المناخية، وانخفاض المساحات المزروعة، وارتفاع تكاليف الإنتاج، وانخفاض حجم الاستثمارات الزراعية، وانخفاض حجم الإنفاق الحكومي في هذا القطاع، وتغيير سياسة دعم مستلزمات الإنتاج، والاستخدام المحدود جدا لطرق الري الحديثة. ومن أجل استعادة هذا القطاع لمكانته في الاقتصاد السوري لابد من التوسع الرأسي والأفقي في عمليات الإنتاج الزراعي، والاستخدام الأوسع لوسائل الري الحديثة، وتوفير الدعم المالي اللازم، وتشجيع الاستثمارات اللازمة، والترابط والتكامل بين السياسات الزراعية والمائية. The agricultural sector is an important component of the Syrian economy as it is the main source of agro-food products. Its output has witnessed significant fluctuations in recent years. This is due to the deterioration in climate conditions, the reduction in cultivated land, the increase in production costs, the decline in agricultural investment, the decrease in government spending in this sector, changing production subsidies policy, and the  very limited application of the new irrigation methods. For the agricultural sector to retain back its role in the Syrian economy, vertical and horizontal expansion of the production operations are needed. In addition, extensive use of new irrigation methods, provision of financial support, encouragement of investment, and the alignment and integration between agriculture and irrigation polices, are necessary.